2016
DOI: 10.21664/2238-8869.2016v5i2.p196-213
|View full text |Cite
|
Sign up to set email alerts
|

Click Bait: You Won’t Believe What Happens Next!

Abstract: O presente capítulo objetiva investigar o fenómeno do Click Bait: uma das estratégias mais utilizadas por alguns jornalistas da atualidade para tornar os títulos das notícias (headlines) mais atrativos aos olhos dos leitores, avaliando os seus impactos na comunidade online. Em primeiro lugar, o capítulo estuda as redes sociais, debruçando-se sobre o poder que estas facultam aos profissionais de marketing na publicação, difusão e partilha da informação. Em seguida, o fenómeno do Click Bait é contextualizado his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 4 publications
1
7
0
3
Order By: Relevance
“…1 Thus, Experiment 1 revealed that change references can affect information seeking in the real world. Because people are most likely to click on online content when that content sparks curiosity (Alves et al, 2016;Kuiken et al, 2017;Rosenkrans, 2010), these results provided initial evidence consistent with our theorizing.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…1 Thus, Experiment 1 revealed that change references can affect information seeking in the real world. Because people are most likely to click on online content when that content sparks curiosity (Alves et al, 2016;Kuiken et al, 2017;Rosenkrans, 2010), these results provided initial evidence consistent with our theorizing.…”
Section: Resultssupporting
confidence: 83%
“…These advertisements varied only in whether they indicated that a focal entity had or had not changed. We examined the impact of this change reference on click-rates because of their theoretical relevance to the current investigation—a primary determinant of whether people click on online content is whether that content evokes curiosity (i.e., an immediate desire to learn more; Alves et al, 2016; Kuiken et al, 2017; Rosenkrans, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…In the news industry, in particular, there has been a real battle for users’ attention. In this industry, headlines are a well‐known and proven means of attracting user clicks (Alves, Antunes, Agrici, Sousa, & Ramos, ; Kim, Mantrach, Jaimes, & Oh, ; Piotrkowicz et al, ). This raises the question, how should headlines be designed to attract the attention of individuals and thus draw them to the content?…”
Section: Influencing Factorsmentioning
confidence: 99%
“…In the course of the headlines’ main task to draw attention to the content, so‐called “clickbait” is also mentioned in the literature (Alves et al, ; Chen, Conroy, & Rubin, ; Kuiken et al, ; Potthast, Köpsel, Benno, & Hagen, ). This method of attracting attention is regarded as a negative influence and partly as a form of spam (Potthast et al, ).…”
Section: Influencing Factorsmentioning
confidence: 99%
“…Los avances en comunicación digital, han promovido modificaciones notables y profundas tanto en la promoción como en la difusión (Alves et al, 2016), así como en lo relativo a los planes y a la efectiva práctica comercial del sector. La acción de las nuevas tecnologías de la comunicación digital invade la propia experiencia del viaje gracias a la telepantalla moderna: los dispositivos móviles con aplicaciones de geolocalización capaces de asistir al viajero en términos vitales y accesorios.…”
Section: Siguiendo a César-arnaiz Y Arnaiz-burne (2016)unclassified